L'Inde de 1919 à 1941 : nationalismes, « communalisme », prosélytisme et fondamentalisme - Marc Gaborieau (Revue des Mondes Musulmans et de la Méditerranée)
The définitive rupture between Hindus and Muslims occurred, on the political level, during the interwar period in 1930, after the philosophical poet, Iqbâl (1876-1938), called for a separate state for Muslims whose name (Pakistan) was invented as early as 1935. An ideological break had preceded the political rupture. The Hindu right had already forged the notion of « Hinduism » (hindutva) as early as 1923, a claim founded on the rejection of medieval Muslim India, i.e. Mughal India. The Muslims fought back, in particular, through the person of Mawdûdî (1903-1979) who, in his first book in 1927, eulogised the war jihâd and tried to rehabilita-te medieval Islam in its pureness and aggressiveness. These writings carried the seed for the Jamâ'at-i Islâmî, a militant organisation which was formally organised in 1941. Deterioration in the relations between the two religious communities went hand in hand with this double rupture : this confrontation was known as « commu-nalism » in Anglo-Indian parlance. Proselyte missionary organisations were created in the two communities, including the Tablîghî Jamâ'at for Muslims in 1927.